Historical development of veterinary pathology in turkey (1842-2002) - Aşkın Yaşar; Atilla Özgür; Rahşan Özen (Eurasian Journal of Veterinary Sciences)
In the first sixty years (1842-1904) of veterinary medicine education and training in scientific sense in Turkey, pathology education was provided in Vetennary Medicine Military School under name of Tesrih-i Marazi" since 1905 and together with "ilm-i Ensac" between 1913 and 1921. It is also know that in the period between 1908 and 1921, pathology course was provided in Civilian Veterinary Medicine School. In scope of historical development of veterinary medicine education in Turkey, this study aims to determine history ol veterinary medicine pathology, which is a bridge between different fields of veterinary medicine practices, and analyze its contribution to science at national and international level in terms of pathology education and training, educating scientists as well as research and scientific publications. The study was considered in context of classical history methodology. It was determined that veterinary medicine researches in Turkey had produced the following output: one book and 19 Turkish articles between "1923-1932"; 16 books and 21 Turkish arid two foreign language articles between 1933-1947 and 30 books. 75 Turkish and 64 foreign language articles between 1948-1973. It was found that the Health Sciences Institutes in Ankara, Firat, Selçuk, Istanbul, Uludağ and Yuzuncuyil Universities awarded total 55 PhD and 4 M.Sc. degrees on veterinary medicine. It was detected that 16 assistant professors, 13 associate professors and 13 professors (total 42} and 23 research assistants were working in all veterinary me<ficine faculties as of 2002. As a result, it can be suggested that pathology field, which has a regular progress as scientific and academic structure in veterinary medicine education, demonstrates the same progress in academic staff structure and graduate education.